The Combination of Afatinib and Bevacizumab in Untreated EGFR-Mutated Advanced Lung Adenocarcinoma: A Multicenter Observational Study - Hsu, Ping-Chih (Pharmaceuticals (Basel), 2020)
The efficacy of afatinib in combination with bevacizumab in untreated advanced epidermal growth factor receptor (EGFR)-mutated lung adenocarcinoma is currently unclear. We sought to investigate the efficacy of this combination through a multicenter observational analysis. Data for 57 patients with advanced EGFR-mutated lung adenocarcinoma who received afatinib combined with bevacizumab as first-line therapy at the Chang Gung Memorial Hospitals in Linkou and Kaohsiung and Taipei Tzu Chi Hospital from May 2015 to July 2019 were analyzed. The objective response rate and disease control rate of afatinib combined with bevacizumab therapy were 87.7% and 100%, respectively. In all patients, the median progression-free survival (PFS) and overall survival (OS) were 23.9 (95% confidence interval (CI) (17.56–29.17)) and 45.9 (95% CI (39.50–53.60)) months, respectively. No statistical significance between exon 19 deletion and L858R mutations was noted in PFS or OS. The most frequent adverse events (AEs) were diarrhea (98.2%) and dermatitis (96.5%), and most AEs were grade 2 or lower and manageable. The combination of afatinib and bevacizumab is an effective therapy for untreated advanced EGFR-mutated lung adenocarcinoma with acceptable safety. Future prospective studies focusing on this combination for untreated advanced EGFR-mutated lung adenocarcinoma are warranted.